Determinants of the degree of functional aortic regurgitation in patients with anatomically normal aortic valve and ascending thoracic aorta aneurysm. Transoesophageal Doppler echocardiography study. Issue 2 (28th February 2008) - La Canna, G; Maisano, F; De Michele, L; Grimaldi, A; Grassi, F; Capritti, E; De Bonis, M; Alfieri, O
Abstract : Objectives: To identify functional aortic regurgitation (FAR) determinants in patients with ascending thoracic aortic aneurysm (ATAA) and surgically confirmed normal aortic valve anatomy. Design: Case–control study. Setting: Non-invasive Cardiology and Cardiac Surgery Department. Patients: Eighty-nine patients with ATAA and varying degrees of FAR undergoing surgery, 40 age-matched patients with ATAA without aortic regurgitation and 20 normal control subjects. Interventions: Doppler and two-dimensional transoesophageal echocardiography. Main outcome measures: Vena contracta (VC) of aortic regurgitant jet, diastolic tented area and coaptation height (CH) of aortic valve leaflets, aortic dimension indexes—Valsalva sinus, sinotubular junction (STJ), tubular tract, annulus (A), STJ/A ratio. Results: When VC was used, a wide range of FAR was seen (mean (SD) 5.59 (2.59) mm, ranging from 2 to 13 mm). Of the variables tested, the most strongly associated with FAR severity in multivariate analysis was diastolic leaflet tenting, measured as CH ( R 2  = 0.69) (sensitivity 98%, specificity 95% using a cut-off value of CH ⩾1.1 cm). In turn, the diastolic leaflet tenting was strongly identified by the STJ/A ratio (sensitivity 87%, specificity 71% using a cut-off value of STJ/A >1.66). Conclusion: The diastolic tenting of aortic leaflets is strongly related to FAR severity in patients with ATAA. The mismatch of STJ/A is significantly associated with diastolic leaflet tenting and its correlated valve regurgitation, independently of the actual ATAA dimension. These findings provide new insight into the mechanism of FAR arising from ATAA.